2017
DOI: 10.21799/frbp.wp.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Identification Through Heterogeneity

Abstract: We analyze set identification in Bayesian vector autoregressions (VARs). Because set identification can be challenging, we propose to include micro data on heterogeneous entities to sharpen inference. First, we provide conditions when imposing a simple ranking of impulse-responses sharpens inference in bivariate and trivariate VARs. Importantly, we show that this set reduction also applies to variables not subject to ranking restrictions. Second, we develop two types of inference to address recent criticism: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The DSGE‐SVAR estimate is consistent with other estimates of multipliers that use variation in defense spending: Ramey (, p. 31) estimates a 5‐year cumulative multiplier of 1.2. Amir‐Ahmadi and Drautzburg (, Figure 4.13) identified an interval of 1.0 to 3.0 consistent with macro sign restrictions and industry‐level heterogeneity restrictions at the 5‐year horizon.…”
Section: Resultsmentioning
confidence: 68%
“…The DSGE‐SVAR estimate is consistent with other estimates of multipliers that use variation in defense spending: Ramey (, p. 31) estimates a 5‐year cumulative multiplier of 1.2. Amir‐Ahmadi and Drautzburg (, Figure 4.13) identified an interval of 1.0 to 3.0 consistent with macro sign restrictions and industry‐level heterogeneity restrictions at the 5‐year horizon.…”
Section: Resultsmentioning
confidence: 68%
“…This paper contributes to a small but growing literature on the Bayesian analysis of partially-identified models, including Poirier (1998), Gustafson (2005), Richardson et al (2011), Moon and Schorfheide (2012), Kitagawa (2012), Hahn et al (2016), Kline and Tamer (2016), and Gustafson (2015). Some recent contributions to the literature on structural vector autoregression models (Amir-Ahmadi and Drautzburg, 2016;Arias et al, 2016;Baumeister and Hamilton, 2015) also explore related ideas. Our results also relate to a large literature on estimating the effect of mis-measured binary regressors.…”
Section: Introductionmentioning
confidence: 90%
“…The previous section showed that bounds on the FEVD reduce the identified set for small-scale models. However, there is a well-known trade-off between sharp identification and computation (Uhlig, 2017;Amir-Ahmadi and Drautzburg, 2018;Giacomini and Kitagawa, 2018;Gafarov, Meier, and Olea, 2018). In fact, tight restrictions can potentially lead to sets with zero measure, or empty sets; thus, it is crucial to distinguish when the identification is sharp because the identified set has a reduced but positive measure, and when constraints are too tight and lead to empty sets.…”
Section: Non-emptiness and Reduction Of The Identified Setmentioning
confidence: 99%
“…Remarkably, nondogmatic bounds on the FEVD identify structural parameters more successfully than sign restrictions and deliver very informative results. The paper shows the approach here is also more effective than alternative strategies of set-reduction, including standard equality restrictions on the FEVD, narrative sign restrictions (Antolín-Díaz and Rubio-Ramírez, 2018;Ludvigson, Ma, andNg, 2018, 2019), constraints on the monetary policy equation (Arias, Caldara, and Rubio-Ramirez, 2019) and the ranking of IRFs (Amir-Ahmadi and Drautzburg, 2018).…”
Section: Introduction and Related Literaturementioning
confidence: 95%
See 1 more Smart Citation